CONSUMPTIVE BEHAVIOR IN ONLINE SHOPPING ON BEAUTIFUL DATES THROUGH SHOPEE’SSITE - Dewi Maria Herawati; Fitriana Pangesti (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
Consumptive behavior that occurs in society occurs because of increasingly rapid technological advances and the many kinds of marketplaces. The trend of usage and penetration rate of e-commerce in Indonesia in 2017-2023 grew very significantly in recent years, especially during the last pandemic. With activity restrictions, people shop online once a month. Based on the results of research by Harbolnas.com, it shows that the National Online Shopping Day Transaction (Harbolnas), a three-day internet shopping event, recorded transactions of Rp. 4.7 trillion, up 42 percent (Rp. 1.4 trillion) from last year's event. From this background, this study aims to find out how consumptive behavior is in shopping online on beautiful dates through the Shopee site. The research method used is descriptive qualitative, while the data collection technique in this study uses Snowball and is obtained through interviews. The results of this study found that the occurrence of consumptive behavior in society was motivated by factors, namely external factors, including culture, family. And internal factors include motivation and economic conditions. Online shopping activities are carried out to meet needs and buy products based on discount shopping vouchers in the form of free shipping vouchers and cashback on beautiful dates given by Shopee. Thus, people become consumptive because they buy goods not based on needs but desires.Keywords: Consumptive Behaviour; Online Shopping; E-Commerce